VISCERAL ADIPOSITY INDEX (VAI) IN TYPE II DIABETES MELLITUS (DM) AND ITS CORRELATION WITH MICROVASCULAR COMPLICATIONS - HULKOTI, VIDYASHREE S.; Acharya, SOURYA; kumar, SUNIL (International Journal of Psychosocial Rehabilitation, 2020)
Obesity like an iceberg phenomenon is causing a large amount of cardiovascular metabolic disorders, it is crucial to identify an ideal index to quantify the risk and prognosis associated with diabetes. Visceral Adiposity Index along with the simple anthropometric data and lipid profile can be a simple yet effective parameter to evaluate the relationship between obesity and diabetes and can also explain the magnitude of various microvascular complications of diabetes, thus navigating the management of morbidity and mortality associated with it. VAI will help in decreasing the burden of obesity and diabetes mellitus in the society.